Acrylated Biopolymers Derived via Epoxidation and Subsequent Acrylation of Vegetable Oils - Yee Heng Ho; Anupreetha Parthiban; Min Chyong Thian; Zhen Hong Ban; Parthiban Siwayanan (International Journal of Polymer Science)
Chemically modified vegetable oils have become commercially attractive nowadays because they can be utilized as specialized components for the production of bioplasticizers and biopolymers due to their characteristics as being inexpensive, nontoxic, biodegradable, and renewable products. Due to the presence of unsaturation sites in the vegetable oils, they can be chemically modified and transformed into polymeric monomers such as acrylated epoxidized vegetable oils through well-known processes like epoxidation and acrylation processes. Acrylated epoxidized vegetable oil is a biopolymer that has a multitude of applications and is used mainly as a coating material for plastic, paper, and wood. There is an enormous demand for this biopolymer, and the market growth prospects are huge in some regions of the world. However, there are some challenges in the synthesis of acrylated epoxidized vegetable oils in achieving the performance of similar acrylated polymer derived from petroleum sources. In this paper, the chemical structure, properties, and chemical modifications of different types of vegetable oils were reviewed where the emphasis was given on epoxidation and its subsequent acrylation processes. This paper also highlights four types of epoxidation and their subsequent acrylation processes involving five different vegetable oils.